Autosomal recessive osteopetrosis: mechanisms and treatments - Sara Penna; Anna Villa; Valentina Capo (The Company of Biologists, 2021)
Autosomal recessive osteopetrosis (ARO) is a severe inherited bone disease characterized by defective osteoclast resorption or differentiation. Clinical manifestations include dense and brittle bones, anemia and progressive nerve compression, which hamper the quality of patients' lives and cause death in the first 10 years of age. This Review describes the pathogenesis of ARO and highlights the strengths and weaknesses of the current standard of care, namely hematopoietic stem cell transplantation (HSCT). Despite an improvement in the overall survival and outcomes of HSCT, transplant-related morbidity and the pre-existence of neurological symptoms significantly limit the success of HSCT, while the availability of human leukocyte antigen (HLA)-matched donors still remains an open issue. Novel therapeutic approaches are needed for ARO patients, especially for those that cannot benefit from HSCT. Here, we review preclinical and proof-of-concept studies, such as gene therapy, systematic administration of deficient protein, in utero HSCT and gene editing.